Desevolvimento de uma metodologia de ensaio eletroquímico não destrutivo para avaliação da sensitização nos aços inoxidáveis austeníticos - Herculano, Luís Flávio Gaspar (2004)
The austenitic stainless steels can suffer intergranular attack caused by the carbon segregation on the grain boundaries forming chromium carbides leading to Cr-depletion near grain boundaries regions. This region is then called sensitized. Even with the use of stabilized steels, under certain temperature conditions the carbide segregation to the grain boundaries area can occur. The conventional technique to determine the sensitized area is the Double Loop Eletrochemical Potentiodynamic Reactivation test (DLEPR). This work intends to estimate a new electrochemical cell mode by DLEPR, with the aim to obtaining a more efficient, faster and non-destructive scanning of the welded material. Obtained results with the new electrochemical cell were validated by Optical Microscopy (OM), Scanning Electron Microscopy (SEM). After the validation, the results indicated that the new methodology was efficient in the sensitized material identification. This new methodology permits that the non-destructive tests be realized in industrial field.